Are Financial Distress and Firm Characteristics Restrict The Operatin Segment Disclosure in Marine Industry? - Sri Ruwanti; Prima Aprilyani Rambe (AFEBI Accounting Review, 2019)
This study aims to examine the effect of financial distress and several factors on company characteristics, firm size, audit quality and public ownership at the level of disclosure of operating segments in marine companies listed on the Indonesia Stock Exchange. 24 populations were observed from 2013 to 2017 and obtained a sample of 10 marine sector companies with purposive sampling method. Observation results obtained an average operating segment disclosure rate of 69%. We found companies with financial difficulties limiting disclosure of operating segments. We also find public ownership influencing the level of disclosure of operating segments. However, it failed to prove the effect of firm size and auditor quality on the operating segment disclosure level